2012
DOI: 10.5402/2012/248989
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatment and Composition Variations on Microstructure, Hardness, and Wear Resistance of C 18000 Copper Alloy

Abstract: The hardness and wear behavior properties of two C 18000 copper alloys with variations in Ni, Si, and Cr concentrations, both within the range of C18000 chemical analysis standard, were studied after the alloy samples had been prepared by melting and casting in sand molds and then heat-treated in solution using two-stage aging for different heating time periods. The results obtained from sample sets of the aforementioned two alloys, and , show that the alloy , with slightly higher Si and Ni and lower Cr conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…But after thermal ageing at elevated temperature especially near recrystallization, the atoms could rearrange themselves because of higher atomic mobility at a higher temperature. As a result, the UTS values of the sample materials have fallen down remarkably at the ageing temperature of 400°C and 450°C as to the fall of strength observed earlier by the authors 43 and also by Alisha et al 44 and Osorio-Galicia et al 45…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…But after thermal ageing at elevated temperature especially near recrystallization, the atoms could rearrange themselves because of higher atomic mobility at a higher temperature. As a result, the UTS values of the sample materials have fallen down remarkably at the ageing temperature of 400°C and 450°C as to the fall of strength observed earlier by the authors 43 and also by Alisha et al 44 and Osorio-Galicia et al 45…”
Section: Resultssupporting
confidence: 67%
“…But after thermal ageing at elevated temperature especially near recrystallization, the atoms could rearrange themselves because of higher atomic mobility at a higher temperature. As a result, the UTS values of the sample materials have fallen down remarkably at the ageing temperature of 400°C and 450°C as to the fall of strength observed earlier by the authors 43 and also by Alisha et al 44 and Osorio-Galicia et al 45 Effect of strain rate on UTS. Since work-hardened sample materials have shown their maximum strength at the ageing temperature of 150°C from the test series with the strain rate of 10 −3 s −1 , further tensile tests have been carried out with the variation of strain rate for the samples aged at 150°C temperature, and the results clearly demonstrate that the tensile strength of all four materials is highly influenced by the strain rate applied with the UTM during the test.…”
Section: Stress-strain Behaviour Of the Materialssupporting
confidence: 63%
“…The stable γ phase precipitate has an equilibrium b.c.c. structure [8,[14][15][16][17][18][19]. Few studies have been done on the effect of cold rolling on the hardening behavior of Cu-Be alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The wear resistance of special brasses was investigated by many researches and was found to be influenced by a few factors: relative proportions of α and β phases, solution hardening mainly affected by the presence of aluminum and overall hardness of the alloy [3,5,11]. Sun et al found that a great amount of nano-sized Mn 5 Si 3 precipitates dispersed in the microstructure of one type of brass containing Mn and Si after quenching at temperatures above 730 o C. It was widely believed that the dispersion of fine precipitates in the matrix could effectively increase hardness and wear resistance of the alloys [12][13][14][15]. However, the effect of nano-sized Mn 5 Si 3 precipitates on the wear behavior of special brasses has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%